Toll-Like Receptors as Modulators of Mesenchymal Stem Cells - DelaRosa, Olga; Dalemans, Wilfried; Lombardo, Eleuterio (Frontiers in Immunology, 2012)
Mesenchymal stem cells (MSCs) have differentiation and immunomodulatory properties that make them interesting tools for the treatment of degenerative disorders, allograft rejection or inflammatory and autoimmune diseases. Biological properties of MSCs can be modulated by the inflammatory microenvironment they face at the sites of injury or inflammation. Indeed, MSCs do not constitutively exert their immunomodulating properties but have to be primed by inflammatory mediators released from immune cells and inflamed tissue. A polarization process, mediated by pattern recognition receptors (PRRs), towards either an anti-inflammatory or a pro-inflammatory phenotype has been described for MSCs. PRRs, including Toll-like receptors (TLRs) and NOD-like receptors (NLRs), have been linked to allograft rejection and the perpetuation of chronic inflammatory diseases (e.g. Crohn´s disease, rheumatoid arthritis) through the recognition of conserved pathogen-derived components or endogenous ligands (danger signals) produced upon injury. Interest in understanding the effects of PRR activation on MSCs has greatly increased in the last few years since MSCs will likely encounter PRRs ligands at sites of injury, and it has been proven that the activation of PRRs in MSCs can modulate their function and therapeutic effect.